Gender Perception Analysis of Istanbul University Law Faculty Students within the Framework of Developing a Law Education Model Based on Gender Equality - Sevtap Metin; Ülker Yükselbaba; Sevgi Kayak; Verda Neslihan Akün (İstanbul Hukuk Mecmuası)
Our study aims to measure the gender perception of law students and to propose tools that will eliminate gender inequality in law education. The law, as an institution that seeks to achieve justice, must also eliminate gender-based injustices, and “If law stands for justice, it must be justice for all.”2 Whether the perception of law and gender has anything to do with law education is an issue that needs to be surveyed. Is it possible for law education to try to change the patriarchal understanding of gender, or is this field entirely up to the personal preferences of the lawyers? In other words, is law education at the level that would provide lawyers with an egalitarian perception of gender? There is no original study on this subject involving students enrolled at law departments in Turkey. Therefore, determining the situation of gender perception in law departments is the first step in developing gender-sensitive education models. This study aims to measure the gender perceptions of Istanbul University Faculty of Law students. For this purpose, the Gender Perception Scale (GPS), developed and proven to be valid and reliable by Altınova and Duyan (2013), was used to determine and evaluate the gender perceptions of the respondents. In addition to the 25-question survey (quantitative), we prepared an eight-question survey (8 qualitative) specifically for law students. In this study, a survey (quantitative and qualitative) was conducted with the voluntary participation of 524 students (there was an “informed voluntary consent form” at the beginning of the survey text). As a result of the quantitative survey, it was concluded that the gender perception of law students at the Istanbul University Faculty of Law ranked quite high in a positive direction. This result was also confirmed by the answers received for the qualitative questions.